현미밥 식감이 부드러운 중생종 벼 ‘보드라미’ - 김우재(Woo-Jae Kim); 강경호(Kyeong-Ho Kang); 정종민(Jong-Min Jeong); 모영준(YoungJun Mo); 김보경(Bo-Kyeong Kim); 정지웅(Ji-Ung Jeung) (Korean journal of breeding, 2019)
‘Bodrami’ is a brown rice cultivar suitable for cooking, developed by crossing ‘Hwaseong’ and ‘Congsengla’ cultivars at Rural Development Administration, Korea, in 2003. Cooked brown rice of ‘Bodrami’ naturally has a soft texture, and after 24 hours of warm treatment, it maintained its soft texture and it was evaluated that the taste and texture of cooked brown rice were better than that of another rice cultivar. ‘Bodrami’ is a mid-maturing rice cultivar. The average heading date in ordinary planting was August 11th in Suwon, Korea, which also exhibits strong to blast leaf and rice stripe virus, and brown rice yield of ‘Bodrami’ had a yield of 5.56 MT/ha in ordinary planting. The advantages of eating brown rice are high intake of GABA (which is excellent for controlling blood), γ-oryzanol (which is good for Antioxidation), rice embryos (rich in fiber), and rice bran (rich in minerals). Another advantage of ‘Bodrami’ is that, compared to glutinous rice varieties (which is a higher glycemic index), it has a lower glycemic index and a smooth texture. The consumption of white rice has been decreasing recently, while interest in brown rice has been increasing as a consequence of these advantages. ‘Bodrami’ was developed in response to recent changes in consumption preferences. (Registration No. 5644) KCI Citation Count: 1